2021
DOI: 10.15252/emmm.202114554
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of a polyglucosan storage disorder by enhancement of autophagic glycogen catabolism

Abstract: This work employs adult polyglucosan body disease (APBD) models to explore the efficacy and mechanism of action of the polyglucosan‐reducing compound 144DG11. APBD is a glycogen storage disorder (GSD) caused by glycogen branching enzyme (GBE) deficiency causing accumulation of poorly branched glycogen inclusions called polyglucosans. 144DG11 improved survival and motor parameters in a GBE knockin (Gbeys/ys) APBD mouse model. 144DG11 reduced polyglucosan and glycogen in brain, liver, heart, and peripheral nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Importantly, the metabolic regulator Sirt-1 pathway, dependent on NAD + availability, is clearly upregulated in the presence of GHF201 which impacts on both the mitochondrial and lysosomal branches. Knowing that GHF201 targets the lysosomal marker LAMP-1 and in turn reduces glycogen accumulation (see difference in glycogen metabolite node size between groups) it becomes apparent that the compound's effect is mostly associated with the lysosomal-autophagy axis as previously demonstrated in APBD models 13 . This autophagy promoting activity might directly increase the ETC rate and ATP production, which in turn improves NAD + /NADH ratio (see Figure 4) activating Sirt-1 deacetylase activity in the GSD1a disease phenotype.…”
Section: The Interaction Between Multiple Phenotypic Features In Gsd1...mentioning
confidence: 71%
See 2 more Smart Citations
“…Importantly, the metabolic regulator Sirt-1 pathway, dependent on NAD + availability, is clearly upregulated in the presence of GHF201 which impacts on both the mitochondrial and lysosomal branches. Knowing that GHF201 targets the lysosomal marker LAMP-1 and in turn reduces glycogen accumulation (see difference in glycogen metabolite node size between groups) it becomes apparent that the compound's effect is mostly associated with the lysosomal-autophagy axis as previously demonstrated in APBD models 13 . This autophagy promoting activity might directly increase the ETC rate and ATP production, which in turn improves NAD + /NADH ratio (see Figure 4) activating Sirt-1 deacetylase activity in the GSD1a disease phenotype.…”
Section: The Interaction Between Multiple Phenotypic Features In Gsd1...mentioning
confidence: 71%
“…Lysosomal pH ratiometric measuring. Ratiometric analysis of Lysosensor dye labeling for lysosomal pH was analyzed using ratiomeric fluorimetry by confocal microscopy analysis as described previously 13 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, is not sufficient to suggest variations in the treatment, as the main purpose of clinical transplants is to save the graft rather than preventing transient, non-progressive histological changes. Likewise, while it seems reasonable to try to alleviate the irreversible permanent PG storage in secondary glycogen storage disease (SGSD) by using molecules that bind to the lysosomal membrane protein (LAMP-1) [ 26 ] in order to enhance autophagic glycogen catabolism [ 27 ], this would not be recommended for a non-progressive and reversible lesion such as drug-induced GGG.…”
Section: Discussionmentioning
confidence: 99%
“…GSD IV (also known as Anderson disease) is caused by abnormal glycogen accumulation because of the decreased activity of glycogen branching enzyme (GBE) [ 224 ]. Akman and colleagues developed a Gbe1 ys/ys mouse model [ 225 ] and Yi and co-workers used the recipient for AAV9 containing the GBE human expression cassette (AAV-GBE). Evaluation of the effectiveness of gene therapy in GSD IV showed that AAV treatment reduced damage and improved liver performance and muscle functions [ 226 ].…”
Section: Glycogen Storage Diseasesmentioning
confidence: 99%